Ana María T. Rodríguez y Rocío Guadalupe Sánchez (Comps.) Los “indios de la Pampa” a través de la mirada misionera: un relato fotográfico del “dilatado yermo pampeano.” (Quinto Sol, 2021)
Reseña
Keywords: Reseña